Ecological Ethics in Islamic Religious Education Textbooks: A Qualitative Representation Analysis - Rahman, Rini; Ismail, Feiby; Nurhayati, Nurhayati; Abu Nazar, Irfan (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
Environmental conservation issues have become a central concern in the discourse of Islamic education, particularly in efforts to internalize sustainability values into Islamic Religious Education (IRE) learning in higher education. This article aims to analyze the representation of ecological conservation values in two commonly used IRE textbooks, employing a qualitative analysis approach grounded in Islamic ecotheology. Data were obtained through document analysis of the IRE textbook published by the Ministry of Research, Technology, and Higher Education (Kemenristekdikti) and the textbook authored by Dr. Nurhasanah, as well as through Focus Group Discussions (FGDs) with five IRE lecturers from four universities. The findings indicate that conservation values are more dominantly presented implicitly, with the category of "Khalīfah and Trust (Khalīfah and Amānah)" emerging as the most prominent narrative, while "Ecological Spirituality" receives minimal explicit attention. These differences in presentation style yield important pedagogical implications, especially regarding the lecturer's role in interpreting implicit values. The contribution of this article lies in offering the Islamic ecotheology framework as both an analytical and pedagogical approach to strengthening value-based sustainability education within the Islamic tradition. These findings underscore the importance of transforming the IRE curriculum from a normative narrative to a more contextual and reflective, transformative approach.